2006
DOI: 10.1007/s00192-006-0194-7
|View full text |Cite|
|
Sign up to set email alerts
|

Spontaneous closure of vesicovaginal fistulas after bladder drainage alone: review of the evidence

Abstract: A vesicovaginal fistula may occur as a surgical complication, the result of obstructed labor, or a late manifestation of radiotherapy. Surgical treatment includes many routes and techniques, with a success rate reaching 100%. The spontaneous closure of vesicovaginal fistulae following [corrected] bladder drainage alone for varying periods has been reported by many. The factors favoring the success of this conservative method have not been well examined [corrected] In this investigation [corrected] all articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 41 publications
0
15
0
3
Order By: Relevance
“…In the cases of fistulas formed due to obstetric or gynecological injuries, spontaneous healing is described in the literature, especially in those cases where the fistula is small and early, with prolonged bladder drainage is provided. [6] Our case does bring out a fact that is less emphasized in the medical teaching that while persistence of fistula is often attributed to the distal obstruction, closure of fistula does not necessarily mean restoration of normal anatomy but could be a development of proximal obstruction. To the best of our knowledge, we are describing the first case of spontaneous closure of the urethrovaginal fistula associated with pelvic fracture.…”
Section: Discussionmentioning
confidence: 84%
“…In the cases of fistulas formed due to obstetric or gynecological injuries, spontaneous healing is described in the literature, especially in those cases where the fistula is small and early, with prolonged bladder drainage is provided. [6] Our case does bring out a fact that is less emphasized in the medical teaching that while persistence of fistula is often attributed to the distal obstruction, closure of fistula does not necessarily mean restoration of normal anatomy but could be a development of proximal obstruction. To the best of our knowledge, we are describing the first case of spontaneous closure of the urethrovaginal fistula associated with pelvic fracture.…”
Section: Discussionmentioning
confidence: 84%
“…The spontaneous closure of VVF without surgical intervention has already been encountered in clinical practice [5]. In this case, it took six months until the fistula was reduced from 1.5 cm to 1–2 mm.…”
Section: Discussionmentioning
confidence: 95%
“…However, the underlying pathophysiology can be identified in almost all cases. Ischemic necrosis of the tissues is the main reason of the fistula formation, hence, obstructed prolonged labor due to unattended deliveries, small pelvic dimensions, malpresentation, poor uterine contractions, introital stenosis, gynecologic surgery, radiation therapy, infectious disease such as lymphogranuloma venereum, tuberculosis, syphilis, bladder stones, retained foreign body in the vagina, obstetrical injury, complications of episiotomy, adolescent deliveries, malnutrition, forceps or vacuum applications, Crohn's disease could lead to genital fistulas [46]. Our study showed that obstetrical factors have been responsible for the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Other reasons include radiation, inflammatory bowel disease, pelvic operations, forceful coitus, and neoplasms. The exact incidence of genital fistulas which is directly related to the socioeconomic level of the affected population is unknown due to data inadequacy in the developing world [2–4]. Genital fistulas can be treated via abdominal or vaginal routes.…”
Section: Introductionmentioning
confidence: 99%